Envisioning holograms : design breakthrough experiences for mixed reality - Pell, M. (Apress, 2017)
Explore the approach, techniques, and mindshift needed to design truly breakthrough experiences for the Microsoft HoloLens and Windows Mixed Reality platform. Learn what's so different about working with holograms, how to think spatially, and where to start designing your own holographic projects. You'll move rapidly from initial concept to persuasive prototype--all without the need for expensive tools or a designer's skill set. Designing for mixed reality is a completely new experience for everyone involved, and takes some experimentation to get right. You won't nail your first mixed reality project by relying upon your previous mobile or web design expertise as a guide. Mixed reality requires a different kind of design thinking for its unique challenges. Breakthrough holographic design starts with envisioning--the act of visualizing what could be. By rapidly depicting a desired experience and trying out its real-world interactions, you can quickly turn your initial vision into a tangible example of innovative design. Envisioning Holograms digs into why holographic computing is the future, takes you through the mixed reality design process, and gets you ready to take advantage of its endless opportunities. What You'll Learn: Understand what makes mixed reality a challenging design space See how envisioning quickly and persuasively brings ideas to life Get to know your audience, medium, and palette Explore several innovative rapid envisioning techniques Identify the key elements of your own holographic experience Design an engaging holographic experience from start to finish.